Incorporating power and assimilating nature: Electric power generation and distribution in Ottawa, 1882--1905 - Adamek, Anna (University of Ottawa (Canada), 2003)
The history of electric power generation and distribution in Ottawa reflects the city's political, economic, and environmental conditions. The process of electrification of the Canadian capital was shaped by strong personalities, by municipal, provincial and federal politics, and by the city's location on the Ottawa River, an interprovincial border. The idea of electrification was introduced by municipal politicians in 1880s as a way of redefining Ottawa as a 'power capital of the Dominion' rather than as the locus of the federal bureaucracy. Yet the process was soon dominated by three powerful Liberals---Thomas Ahearn, Erskine H. Bronson and Warren Y. Soper---who gained influence among the three social groups who constituted the majority of Ottawa residents, Irish Catholics English Protestants, and Methodists. Their strong political influence in the Canadian capital allowed the three industrialists to form alliances within the provincial and federal government to permit them to build an electric empire. By 1894, the year in which they created the Ottawa Electric Company and the Ottawa Electric Railway Company, Ahearn, Bronson and Soper held a monopoly over the city's power generation and distribution. Yet as the three entrepreneurs shaped the electric market and urban development of the city, their endeavours were influenced by the politics, location, and natural resources of the Ottawa area. The same factors that fashioned a strong monopoly, also obstructed it, leading to establishment of a municipal plant in 1905 and consequently creating an electric duopoly in Ottawa.
Keywords: History, Canadian.; Engineering, Civil.; Energy.